Intermittent Hypoxia Training Prevents Deficient Learning-Memory Behavior in Mice Modeling Alzheimer's Disease: A Pilot Study - Ryou, Myoung-Gwi; Chen, Xiaoan; Cai, Ming; Wang, Hong; Jung, Marianna E.; Metzger, Daniel B.; Mallet, Robert T.; Shi, Xiangrong (Frontiers in Aging Neuroscience, 2021)
In mouse models of Alzheimer’s disease (AD), normobaric intermittent hypoxia training (IHT) can preserve neurobehavioral function when applied before deficits develop, but IHT’s effectiveness after onset of amyloid- (A) accumulation is unclear. This study tested the hypothesis that IHT improves learning-memory behavior, diminishes A accumulation in cerebral cortex and hippocampus, and enhances cerebrocortical contents of the neuroprotective trophic factors erythropoietin and brain-derived neurotrophic factor (BDNF) in mice manifesting AD traits. Twelve-month-old female 3xTg-AD mice were assigned to untreated 3xTg-AD (n=6), AD+IHT (n=6), and AD+sham-IHT (n=6) groups; 8 untreated wild-type (WT) mice also were studied. AD+IHT mice alternately breathed 10% O2 for 6 min and room air for 4 min, 10 cycles/day for 21 days; AD+sham-IHT mice breathed room air. Spatial memory-learning was assessed by Morris water maze. Cerebrocortical and hippocampal A40 and A42 contents were determined by ELISA, and cerebrocortical erythropoietin and BDNF were analyzed by immunoblotting and ELISA. The significance of time (12 months vs 12 months + 21 days) and treatment (IHT vs sham-IHT) was evaluated by two-factor ANOVA. The change in swimming distance to find the water maze platform after 21 d IHT (-1.6 ± 1.8 m) differed from that after sham-IHT (+5.8 ± 2.6 m). Cerebrocortical and hippocampal A42 contents were greater in 3xTg-AD than WT mice, but neither time nor treatment significantly affected A40 or A42 contents in the 3xTg-AD mice. Cerebrocortical erythropoietin and BDNF contents increased appreciably after IHT as compared to untreated 3xTg-AD and AD+sham-IHT mice. In conclusion, moderate, normobaric IHT prevented spatial learning-memory decline and restored cerebrocortical erythropoietin and BDNF contents despite ongoing A accumulation in 3xTg-AD mice.